2021
DOI: 10.1097/ajp.0000000000000963
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Epidural Steroid Injections for Lumbosacral Radicular Pain

Abstract: Objective: Epidural steroid injections (ESIs) are a commonly utilized treatment for lumbosacral radicular pain caused by intervertebral disc herniation or stenosis. Although effective in certain patient populations, ESIs have been associated with serious complications, including paralysis and death. In 2014, the US Food and Drug Administration (FDA) issued a safety warning on the risk of injecting corticosteroids into the epidural space. The aims of this article were to review the neurological com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…10 On the other hand, non-particulate steroids, such as dexamethasone preparations, contain little to no particles or have particles that are less than 0.5 µm and are freely watersoluble. 7,10 It is hypothesised that particulate steroids have an increased risk of causing embolisation of arterioles in cases of inadvertent intravascular injection, due to particles or particle aggregates blocking small arterioles supplying the neural parenchyma, leading to ischaemia and infarction. 8,10,11,17,18 For example, in an experimental study on a swine model by Okubadejo et al, it was shown that injection of MPA into the vertebral artery resulted in ischaemic brain injury.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…10 On the other hand, non-particulate steroids, such as dexamethasone preparations, contain little to no particles or have particles that are less than 0.5 µm and are freely watersoluble. 7,10 It is hypothesised that particulate steroids have an increased risk of causing embolisation of arterioles in cases of inadvertent intravascular injection, due to particles or particle aggregates blocking small arterioles supplying the neural parenchyma, leading to ischaemia and infarction. 8,10,11,17,18 For example, in an experimental study on a swine model by Okubadejo et al, it was shown that injection of MPA into the vertebral artery resulted in ischaemic brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroid preparations are frequently used for injection into the epidural space for treatment of radicular pain/radiculopathy in humans and for the non‐surgical management of DLSS in dogs 3,7,11,13 . Injectable corticosteroids can be grouped into two categories based on solubility and/or particle size 10,16 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Complications appear to be rare in veterinary medicine and may relate primarily to sterility and trauma but have also been linked to the formulation (including preservatives and particulation). In human chronic spinal pain management, complications can be severe, and concerns have been raised specifically regarding the use of particulate steroids -like methylprednisoline- when applied epidurally ( 219 ).…”
Section: Treatment Guidelinesmentioning
confidence: 99%